KETIMPANGAN RELASI KUASA DAN PATRIARKI DALAM KEKERASAN SEKSUAL BERBASIS GENDER (PERSPEKTIF SOSIOLOGI DAN HUKUM) - Hartanto Hartanto; Dwi Astuti (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
Sexual violence that occurs in accordance with human civilization, the difference is the act of closing the justification argument, but along with the development of society and science which is later recognized as deviant behavior, and is now a criminal act. In the context of the development of criminal law related to children and women originating from the Child Protection Law, the PKDRT Law, at this time it accommodates sociology expectations of social relations, with the enactment of Law No. 12 of 2022 concerning the Crime of Sexual Violence. This normative juridical research has the urgency to explain the workings of power relations factors in cases of sexual violence against women in a sociological perspective and how the role of law, especially criminal law. In fact, violence is almost certainly gender-based. The law on criminal acts of violence can reduce power relations, in short, the relationship between men and women must continue to develop in a positive direction. Keywords: politics, power relations, violence, politics, gender